Peripheral lymph node tuberculosis: epidemiological characteristics - E. V. Kulchаvenya; E. Yu. Koveshnikovа; M. M. Mergаnov; F. R. Shаripov (Туберкулез и болезни лёгких)
Peripheral lymph node tuberculosis is one of the most frequent extrapulmonary localizations.The objective of the study: to define the place of peripheral lymph node tuberculosis in the structure of extrapulmonary tuberculosis incidence in the neighboring regions with the unfavorable epidemic situation (Siberian and Far Eastern Federal Districts (SFD and FEFD) and the Republic of Tajikistan); to study the structure of this form of tuberculosis.Subjects and methods. The statistic reports from TB units of SFD, FEFD and the Republic of Tajikistan for 2016-2017 were reviewed. The structure of peripheral lymph node tuberculosis was assessed through a retrospective analysis of medical records of peripheral lymph node tuberculosis patients, notified in the Republic of Tajikistan and Regional Novosibirsk TB Dispensary in 2016 and 2017 in total.Results of the study. In 2016-2017 in SFD and FEFD, isolated forms of extrapulmonary tuberculosis were diagnosed in 1,227 patients, of them, 166 (13.5%) patients suffered from peripheral lymph node tuberculosis. In SFD and FEFD of the Russian Federation, our study detected no statistically significant changes in the proportion of peripheral lymph node tuberculosis in the structure of extrapulmonary tuberculosis incidence in the patients with positive and negative HIV status. In the Republic of Tajikistan, the frequency of peripheral lymph nodes tuberculosis among extrapulmonary tuberculosis cases was statistically significantly higher versus SFD and FEFD in the Russian Federation (504/1 386 and 166/1 227 respectively, p < 0.01). In the Republic of Tajikistan, SFD and FEFD of the Russian Federation, tuberculosis of neck lymph nodes was the most frequent in the structure of peripheral lymph node tuberculosis followed by axillary and inguinal localizations. The difference in the frequency of each localization between the compared regions was not statistically significant.